64 Safety and efficacy outcomes of cryoballoon ablation in patients with paroxysmal and persistent atrial fibrillation. (28th September 2016) - O'Neill, L; Tanner, R; Jacobsen, A; McCabe, J; Thornton, J; Cronin, M; Keelan, E; Galvin, J
Abstract : Introduction: Pulmonary vein isolation (PVI) using the method of cryoballoon ablation has been shown to be non-inferior to radiofrequency ablation for treatment of paroxysmal atrial fibrillation (AF) in the recently published 'Fire and Ice' trial. We evaluated the safety and efficacy outcomes of patients undergoing cryoballoon ablation for persistent and paroxysmal AF in a single centre over a four year period. Methods: Retrospective chart review and analysis of procedure notes were performed on patients undergoing cryoballoon ablation between 2012 and early 2016. Recurrence of arrhythmia was based on return of symptoms and documentation of AF on ECG or holter monitor. Results: Sixty four patients were included. AF was persistent in 16 patients. Prior duration of arrhythmia was 5.7–4.6 years. Palpitation was the most common presenting complaint in 40% followed by dyspnoea in 25%. Electrical cardioversion had been performed in 34 patients prior to procedure with 25 undergoing <2 prior cardioversion. Nineteen patients had hypertension and 7 had left ventricular dysfunction. All patients had taken at least one antiarrhythmic agent. Amiodarone was the most commonly prescribed agent in 57%. Waiting time from referral date to procedure date was 10.1–4.2 months. Cryoballoon ablation was undertaken using the Medtronic Arctic Front and Arctic Front Advance catheters. All patients were anticoagulated periprocedurally. Twenty five patients were taking warfarin and the remainder novel oral anticoagulants. Mean procedure time was 107.9 ± 24.2 minutes. The average number of applications was 7 per procedure, each application for a duration of 180–240 seconds. All pulmonary veins were confirmed to be isolated in 47 patients with 3 out of 4 isolated in 10 patients. Electrical cardioversion was performed in 17 patients to restore sinus rhythm at end of procedure. Right phrenic nerve palsy was noted intraprocedurally in five patients. This was clinically significant on follow up in one patient. Mean follow up duration was 20.4 12.1 months. Thirty patients (46.8%) were free from AF at final follow up. Twenty five patients (39%) experienced recurrence of AF with 7 undergoing repeat PVI using radiofrequency ablation. Nine patients currently await redo procedures. Of those who experienced recurrence, prior pattern of AF was paroxysmal in 15 and persistent in 10. Six patients, including patients from both recurrence and no recurrence groups, developed atrial flutter. Follow up data was unavailable for 9 patients. Conclusion: Provisional results from this real world series suggest lower success rates than seen in large scale trials. This may reflect our heterogeneous cohort including patients with persistent atrial fibrillation and the possible effects that long waiting times may have in terms of increasing burden of arrhythmia and consequent adverse left atrial remodelling.